Адміністративні послуги як різновид адміністративного договору - Зуб, Д. М. (ХНУРЕ, 2021)
This article discusses – administrative services as a type of administrative contracts. The main purpose of the author is to consider administrative services as a kind of administrative contracts, to give a clear definition of an administrative service and an administrative contract, to consider the law of Ukraine «On Administrative Services». The author comes to the conclusion that an administrative contract is the final stage of the implementation of a public service by a subject of power in the form of an agreement between the subject of the provision of administrative services and the person who ordered the service
Keywords: філософія; адміністративні послуги